Regional economic planning in Cameroon - Wilfried A. Ndongko (Intereconomics, 1974)
The purpose of this paper is to present a survey of the Cameroonian experience in development planning with emphasis on the regional dimension. In the course of analysing the planning process and implementation, an attempt will be made to shed light on some of the major problems which have been encountered in evaluating the development effort at the regional level.
Keywords: 330; Cameroon